THE PROCESS OF WORD FORMATION AND PHRASE STRUCTURE OF ANDROID APPLICATION NAMES - Handayani, Heny (LANTERN (Journal on English Language, Culture and Literature), 2013)
Android is an operating system for mobile device, such as smartphones and tablet computers that was developed by Google. In this era, android is a popular operating system that is searched by people because of necessary of information. The process and structure of android application names are interesting to be analyzed since they have different structure of words in general. The purpose research is to describe and explain which word formation processes and phrase structure that are commonly used in Android Application Names. In this research, the writer used descriptive qualitative method. The technique to process the data is Teknik Bagi Unsur Langsung. The writer found 100 android application names in android phone with 10 word formation processes that form those; they are 39 words compounding, 21 words multiple processes, 9 words which was formed acronym and initialization, 9 words back formation, 7 words conversion, 5 words clipping, 3 words blending, 3 words borrowing, 3 words inflection, and also 1 word which was formed derivation. Based on the phrase structure, the writer 84 words noun phrase, 15 words verb phrase, and 1 word infinitival phrase. The result shows that noun phrase is frequent phrases that can be found in the android phone.